2023
DOI: 10.3390/healthcare11172399
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of a Physical Exercise Programme Executed through Immersive Virtual Reality

Frano Giakoni-Ramírez,
Andrés Godoy-Cumillaf,
Paola Fuentes-Merino
et al.

Abstract: Evidence suggests that moderate to vigorous physical activity (MVPA) is necessary for health benefits. Immersive virtual reality is a technology that uses images, sounds, and tactile sensations from a simulated world to encourage healthy behaviours and physical activity. The aims of this research are (1) to determine the duration and intensity of physical activity performed through immersive virtual reality; (2) to determine differences in physical activity intensity according to gender. Methods: A nonprobabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, this underestimation is likely due to the placement of the accelerometer (ie, waist-worn), which is unlikely to capture the full range of dynamic upper and lower body movements characteristic of a VR fitness game. Notably, several other studies have used waist-worn accelerometers within VR research [ 25 , 26 ], though these studies have examined time spent in MVPA rather than an energy expenditure outcome (eg, METs). Despite this, an underrepresentation of MVPA as captured by accelerometry still appears to be evident; Sousa et al [ 26 ] reported an average of 4.10 (SD 4.93) minutes of MVPA for a 20-minute VR fitness session (approximately 21%), while Giakoni-Ramirez and colleagues [ 25 ] reported an average of 3.57 minutes of MVPA for a 9-minute “intermediate” VR fitness session (approximately 40%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this underestimation is likely due to the placement of the accelerometer (ie, waist-worn), which is unlikely to capture the full range of dynamic upper and lower body movements characteristic of a VR fitness game. Notably, several other studies have used waist-worn accelerometers within VR research [ 25 , 26 ], though these studies have examined time spent in MVPA rather than an energy expenditure outcome (eg, METs). Despite this, an underrepresentation of MVPA as captured by accelerometry still appears to be evident; Sousa et al [ 26 ] reported an average of 4.10 (SD 4.93) minutes of MVPA for a 20-minute VR fitness session (approximately 21%), while Giakoni-Ramirez and colleagues [ 25 ] reported an average of 3.57 minutes of MVPA for a 9-minute “intermediate” VR fitness session (approximately 40%).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several other studies have used waist-worn accelerometers within VR research [ 25 , 26 ], though these studies have examined time spent in MVPA rather than an energy expenditure outcome (eg, METs). Despite this, an underrepresentation of MVPA as captured by accelerometry still appears to be evident; Sousa et al [ 26 ] reported an average of 4.10 (SD 4.93) minutes of MVPA for a 20-minute VR fitness session (approximately 21%), while Giakoni-Ramirez and colleagues [ 25 ] reported an average of 3.57 minutes of MVPA for a 9-minute “intermediate” VR fitness session (approximately 40%). Hence, our findings suggest that the use of accelerometers during this form of PA be used cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation